Alignment and contribution of nursing doctoral programs to achieve the sustainable development goals - Mendes, Isabel Amélia Costa (2021)
Background: Different social segments from several regions of the world face challenges in order to achieve the sustainable development goals (SDGs). Nursing represents the greatest number of health workforce in the globe, dealing with these challenges in different paths, among them the training of human resources. In this context, the goal of this study was to compare the relationship between the objectives and research areas underlying nursing doctoral programs in Latin America and the SDGs. Method: Documental research comparing data of all Latin American nursing doctoral programs and the SDGs, conducted between January and March 2020. Results: From the total of 56 existing programs in Latin America, this study analyzed 52 of them, representing 92.8% of the total. Most nursing doctoral programs have contributed to SDG 3, in addition to goals 1, 2, 4, 5, 6, 8, 9, 10, 12 and 16. The SDGs 11, 13, 14, 15 and 17 were not related to any of the analyzed programs. Data reveal that the training of nursing PhDs is essential to fulfilling these goals. Results also indicate a need of programs to remain committed to relationships that enhance nursing skills to cope with the current challenges in terms of global health, such as investments for the reduction of social and gender inequities. Conclusion: The doctoral training of nurses in Latin America needs to be better aligned with the sustainable development goals (SDGs), since there is a high concentration in SDG 3. We believe that nursing will bring a greater contribution to the movement to protect planetary health as the principles governing nursing practices are better aligned with international health demands and agendas.